The role of porous structure copolymers as catalytic systems carriers - Kolarz, B. N.; Owsik, I. (Polimery, 2022)
The possibilities of using of crosslinked vinyl copolymers as the carriers of heterogenic catalysts (systems showing properties as of homogenic catalysts and the same time being easy to separate from the post-reaction mixture) have been generally characterized. Special attention had been paid to polystyrene-sulfo-cation exchangers (styrene/divinylbenzene copolymers) (Table 1), used in various types of chemical reactions, as well as to interfacial catalysts (Table 2) and, specially, to enzyme-like catalysts. From the last group, the catalysts containing coordinated metal ion, catalyzing the oxidation reactions, were discussed in details. The results of own investigations concerning the effect of the structure of enzyme-like catalysts, containing guanidine and carboxyl groups [coordinating Cu(II) ions] on the course of oxidation during model reaction of hydroquinone oxidation to p-benzoquinone (Figs. 1 and 2, Tables 3-5) were presented. In new directions of investigations in this field, the research works on molecularly imprinted polymers (MIP) seem to distinguish.